The future of European gas markets : balancing act between decarbonisations and security of supply - Hafner, Manfred (Energy scenarios and policy ;, 2016)
Gas represents a pivotal element of the European energy architecture. New elements such as the evolution of the EU Energy Union, the international climate agreement reached at COP-21, the EU-Russia gas relations in the aftermath of the Ukraine crisis and the supply potential emerging in the Eastern Mediterranean, are rapidly reshaping the European gas markets. This book seeks to provide an insight on these developments, with the ultimate aim of contributing to the current European gas debate by providing a balancing act between two issues, decarbonisation of the European energy system and security of gas supply, that are usually conceived as different and unmatched but that represent, in reality, the two sides of the same coin.